Bionanotechnology II : global prospects - Reisner, David Evans (Boca Raton : CRC Press, 2012)
'The impact and importance of nanotechnology continues to grow, and nanomedicine and biotechnology have become areas of increased development. Biomedical engineers who work with biological processes and structures must have a deeply rooted understanding of the role of bionanotechnology, a rapidly evolving sector of the nanotechnology field. Bionanotechnology II: Global Prospects is a follow-up to the editors highly successful first volume, containing 26 entirely new contributions that provide a broad survey of research shaping this critical field. With coverage of technical and nontechnical areas, the book offers representative reporting on a wide variety of activity from around the world. It discusses the role of nanotechnology in novel medical devices, bioanalytical technologies, and nanobiomaterials.Topics discussed include: Emerging microscale technologies, bionanotech-based water treatment, tissue engineering and drug delivery, antimicrobial nanomaterials in the textile industry, bionanotechnology applications in plants and agriculture, with contributions from researchers in Israel, Egypt, Iran, Jordan, Singapore, South Africa, Turkey, Thailand, Argentina, the United Kingdom, and the United States. This volume presents a worldwide perspective on some of the critical areas shaping bionanotechnology today'--Provided by publisher.
Keywords: Nanotechnology; Biotechnology